STUDI KASUS: GANGGUAN MENELAN PADA PASIEN AKALASIA ESOFAGUS - Agianto; Aisyah; Muhlisoh; Riyadi, Efrin; Zahratunnisa, Enny; Silvia, Mega; Zahratun, Azizah; Nor'aina, Mutia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Esophageal achalasia, or also known as simple ectasia, cardiospasm, mega esophaageal, is one ofthe rare disease. In the General Hospital of Ulin Banjarmasin, this case is a rare.According toinformation that obtained from male internist ward, this case is the first time in there. The clientcomplained that he could not ate and drank since three months ago. Clientinitially complained that hefelt there was different sense in the throat. When heswallowed, he directly got vomiting. Thecharacteristics of vomiting was what he had eaten and drank. Client also complained that aftervomiting, he felt pain and sour at throat. Nursing diagnosis that appears on the client was associatedwith swallowing disorder related to (r/t)achalasia disease (disturbance / damage to the esophagus);imbalance nutrition: less than body requirements r/t biological factors: inability to have nutritionalintake (interference / damage of esophagus); risk for lack of fluid volume with risk factors: excessivefluid loss: vomit fluid / food; deficiency of knowledge r/t the lack of information exposure (esophagealachalasia), and acute pain r/t biological injury agents (disease: esophageal achalasia).